Experiences of family members of people with mental disorders - Luana Idalino da Silva; Álissan Karine Lima Martins; Kariny Kelly de Oliveira Maia; Francisca Bezerra de Oliveira; Ângela Maria Alves e Souza (Universidade Federal do Ceará, 2014)
The study aims at knowing the experiences of family members of people with mental disorders in small-sized counties in the countryside of the state of Paraíba, Brazil. This is an exploratory research with qualitative approach made with 14 family members of people with mental disorders. The data collection took place in February and March 2013 through the technique of oral history of life guided by a semi-structured interview. For data analysis, we used the thematic content analysis. The results showed a significant suffering and difficulties of family members in the care of people with mental disorders, once they feel alone, most often without a family, political or professional support. The overload of these family members was evidenced by the occurrence of chronic diseases, the use of medications, and marital separation. The improvement of the existing health services and the formulation of county policies can promote a better quality of life to these subjects.